Aerobic exercise modulates the free fatty acids and inflammatory response during obesity and cancer cachexia - Teixeira, Alexandre Abilio de S.; Lira, Fábio S. [UNESP]; Pimentel, Gustavo D.; Oliveira de Souza, Camila; Batatinha, Helena; Biondo, Luana A.; Yamashita, Alex S.; Lima Júnior, Edson A.; Rosa Neto, José C. (Begell House, 2016)
White adipose tissue (WAT) is no longer considered a tissue whose main function is the storage of TAG. Since the discovery of leptin in 1994, several studies have elucidated the important role of WAT as an endocrine organ, the source of the adipokines. The low-grade inflammation observed in obese and cancer cachexia patients is explained, at least partially, by the exacerbated release of proinflammatory adipokines. Despite of the recent progress in the characterization of the various adipokines and lipokines produced by WAT, little is known about the mechanisms regulating the secretion of these molecules in different physiological and pathological circumstances. Chronic exercise is a nonpharmacological therapy employed in several chronic diseases and shows an anti-inflammatory effect through the regulation of the cytokine network. In this review, we address the potential mechanisms by which the aerobic physical exercise modulate the production and release of inflammatory adipokines, as well as the inflammation-lipolysis axis in WAT, with special focus in the therapeutic role of exercise in obesity-associated insulin resistance and cancer cachexia.
Keywords: Aerobic exercise; Cancer cachexia; Inflammation; Obesity; White adipose tissue